Access and Non–Access Site Bleeding After Percutaneous Coronary Intervention and Risk of Subsequent Mortality and Major Adverse Cardiovascular Events. (April 2015) - Kwok, Chun Shing; Khan, Muhammad A.; Rao, Sunil V.; Kinnaird, Tim; Sperrin, Matt; Buchan, Iain; de Belder, Mark A.; Ludman, Peter F.; Nolan, James; Loke, Yoon K.; Mamas, Mamas A.
<x xml:space="preserve">Abstract</x> Background— The prognostic impact of site-specific major bleeding complications after percutaneous coronary intervention (PCI) has yielded conflicting data. The aim of this study is to provide an overview of site-specific major bleeding events in contemporary PCI and study their impact on mortality and major adverse cardiovascular event outcomes. Methods and Results— We conducted a meta-analysis of PCI studies that evaluated site-specific periprocedural bleeding complications and their impact on major adverse cardiovascular events and mortality outcomes. A systematic search of MEDLINE and Embase was conducted to identify relevant studies and random effects meta-analysis was used to estimate the risk of adverse outcomes with site-specific bleeding complications. Twenty-five relevant studies including 2 400 645 patients that underwent PCI were identified. Both non–access site (risk ratio [RR], 4.06; 95% confidence interval [CI], 3.21–5.14) and access site (RR, 1.71; 95% CI, 1.37–2.13) related bleeding complications were independently associated with an increased risk of periprocedural mortality. The prognostic impact of non–access site–related bleeding events on mortality related to the source of anatomic bleeding, for example, gastrointestinal RR, 2.78; 95% CI, 1.25 to 6.18; retroperitoneal RR, 5.87; 95% CI, 1.63 to 21.12; and intracranial RR, 22.71; 95% CI, 12.53 to 41.15. Conclusions— The prognostic impact of bleeding complications after PCI varies according to anatomic source and severity. Non–access site-related bleeding complications have a similar prevalence to those from the access site but are associated with a significantly worse prognosis partly related to the severity of the bleed. Clinicians should minimize the risk of major bleeding complications during PCI through judicious use of bleeding avoidance strategies irrespective of the access site used.